Analysis of Critical Thinking Skills of Students Assisted With Nearpod Media on Ecosystem Materials - Wulandari, Ismi Ayu; Maspupah, Meti; Sholikha, Maratus (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
The era of globalization is marked by changes and rapid developments that occur in various fields of life, one of which is in the field of education. This situation becomes a challenge for educators to always develop their abilities. This critical thinking skill becomes important to be appointed and trained in biology learning. Through this research, the aim is to analyze students' critical thinking skills using a blended learning model assisted by nearpod media on ecosystem materials. This study uses a quantitative approach which used method is a quasi-experimental method. The technique for collecting research data is through a description test of ten questions given during the pretest-posttest. Based on the data obtained during the study, it can be concluded thatthe results of critical thinking skills assisted by nearpod media got an average pretest of 55.53 which increased to 78.25 with an N-Gain value of 0.46 medium criteria. Students with critical thinking skills in the high category were 28 students, the medium category was 3 students, and the low category was 2 students.